(3TQM GdeYGde aj CUhd GdOjfs - (3CHh eMeO YHO Gddg Hf eMeO Hf Ydj GdagQi GdeYQha HGHf GdJdeSGfis; (3GdaNQ GdQGRj , GdaNQ GdQGRj,J (B606 (3g` s
(3ChdgG (B:s
(3agPG eNJUQ eTJed Ydi CfhGY ef GdYdhe GdegeI jYfi ai GdOjf bhdg aChdgG Yde CUhd GdOjf s
(3BNQgG (B:s
(3GdMLI GdKGfjI Cf YdjkG QVi Gddg Yfg PcQ LedI GdfUhU GdNajI hGZaQ dfG hGQMefG CfJ ehdfG aGfUQfG Ydi Gdbhe GdcGaQjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
Keywords: (3CUhd Gdabgs